Design of non-selective refocusing pulses with phase-free rotation axis by gradient ascent pulse engineering algorithm in parallel transmission at 7T - Massire, Aurélien; Cloos, Martijn A.; Vignaud, Alexandre; Le Bihan, Denis; Amadon, Alexis; Boulant, Nicolas (Journal of magnetic resonance (1997), 2013)
[Display omitted] ► We report a new MRI radiofrequency pulse design algorithm based on optimal control. ► Spin refocusing non-uniformities are addressed using tailored RF pulses. ► The target rotation matrix is synthesized with a phase-free rotation axis. ► In vitro spin-echo experiments demonstrate the potential of the optimization algorithm. ► Performance obtained is quantified using Quantum Process Tomography. At ultra-high magnetic field (⩾7T), B1 and ΔB0 non-uniformities cause undesired inhomogeneities in image signal and contrast. Tailored radiofrequency pulses exploiting parallel transmission have been shown to mitigate these phenomena. However, the design of large flip angle excitations, a prerequisite for many clinical applications, remains challenging due the non-linearity of the Bloch equation. In this work, we explore the potential of gradient ascent pulse engineering to design non-selective spin-echo refocusing pulses that simultaneously mitigate severe B1 and ΔB0 non-uniformities. The originality of the method lays in the optimization of the rotation matrices themselves as opposed to magnetization states. Consequently, the commonly used linear class of large tip angle approximation can be eliminated from the optimization procedure. This approach, combined with optimal control, provides additional degrees of freedom by relaxing the phase constraint on the rotation axis, and allows the derivative of the performance criterion to be found analytically. The method was experimentally validated on an 8-channel transmit array at 7T, using a water phantom with B1 and ΔB0 inhomogeneities similar to those encountered in the human brain. For the first time in MRI, the rotation matrix itself on every voxel was measured by using Quantum Process Tomography. The results are complemented with a series of spin-echo measurements comparing the proposed method against commonly used alternatives. Both experiments confirm very good performance, while simultaneously maintaining a low energy deposition and pulse duration compared to well-known adiabatic solutions.